2016
DOI: 10.1093/humrep/dew088
|View full text |Cite
|
Sign up to set email alerts
|

Does BPA alter steroid hormone synthesis in human granulosa cellsin vitro?

Abstract: This study was supported by grant number 1936/12 from the Israeli Science Foundation (ISF). The authors have no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
48
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 24 publications
9
48
1
Order By: Relevance
“…These disparities demonstrate that the effects of BPA cannot be extrapolated to make conclusions about BPS or other structurally related substitutes, and that thorough testing is required for each individual chemical. Previous studies have reported that μM concentrations of BPA reduce oestradiol production in rat and human granulosa cells (Mansur et al., ; Zhou et al., ). All of these studies also detected BPA‐mediated alterations in granulosa cell progesterone production, whereas no effects of BPS on progesterone production were found in the current study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These disparities demonstrate that the effects of BPA cannot be extrapolated to make conclusions about BPS or other structurally related substitutes, and that thorough testing is required for each individual chemical. Previous studies have reported that μM concentrations of BPA reduce oestradiol production in rat and human granulosa cells (Mansur et al., ; Zhou et al., ). All of these studies also detected BPA‐mediated alterations in granulosa cell progesterone production, whereas no effects of BPS on progesterone production were found in the current study.…”
Section: Discussionmentioning
confidence: 94%
“…However, to the best of our knowledge, there is no information about whether BPS affects follicular cell function in mammals. BPA is well established to affect female fertility (Ziv-Gal & Flaws, 2016), including altering the function of granulosa cells (Mansur et al, 2016;Mlynarčíková, Kolena, Ficková, & Scsuková, 2005;Xu et al, 2002) and theca cells (Zhou, Liu, Liao, Han, & Liu, 2008) in a variety of species. Although BPS and BPA are structurally related, the two compounds exhibit different potencies for steroid hormone receptors (Rochester & Bolden, 2015) demonstrating that the effects of BPS on female reproduction cannot be inferred from what is known about BPA.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that xenoestrogens can alter granulosa cell steroidogenesis. BPA lowers progesterone biosynthesis and reduces the mRNA levels of Hsd3b1, Cyp11a1 and Cyp19a1 in human granulosa cells (Mansur et al, 2016;Mansur et al, 2017),…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with both animal and in vitro experiments with human luteinized ovarian granulosa cells have demonstrated the ability of bisphenol‐A (BPA) to alter the steroidogenesis in granulosa cells . However most studies to date have not yet elucidated the indirect impact of BPA resulting from maternal exposure, on granulosa cell estrogen biosynthesis in parallel with functionally associated miRNA expression, especially during the reproductively active life of the exposed organism.…”
Section: Introductionmentioning
confidence: 94%